2014
DOI: 10.1007/s00405-014-3216-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of septated concha bullosa on sinonasal pathologies

Abstract: The purpose of this study was to retrospectively determine the possible role of septated concha bullosa on sinonasal pathologies. Paranasal sinus computerized tomography scans of patients with symptoms of headache, postnasal drip, nasal obstruction and smell disorders were retrospectively evaluated. Twenty-eight subjects with unilateral septated concha bullosa and 13 subjects with unilateral concha bullosa without septation were selected as the study and control groups, respectively. Both groups were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Unlu et al 17 suggested that CB does not lead to significant mucosal changes in the paranasal sinuses and does not cause sinusitis alone, similar to others 13,17,18,30 . Another study showed that there was no statistically significant relationship between the presence of CB or NSD and maxillary sinusitis.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Unlu et al 17 suggested that CB does not lead to significant mucosal changes in the paranasal sinuses and does not cause sinusitis alone, similar to others 13,17,18,30 . Another study showed that there was no statistically significant relationship between the presence of CB or NSD and maxillary sinusitis.…”
Section: Discussionmentioning
confidence: 78%
“…Unlu et al 17 suggested that CB does not lead to significant mucosal changes in the paranasal sinuses and does not cause sinusitis alone, similar to others. 13,17,18,30 Another study showed that there was no statistically significant relationship between the presence of CB or NSD and maxillary sinusitis. In Reference 31 the present study, no significant difference was found between the presence of MTCB, NSD grade, and LMS in patients who underwent SRP.…”
Section: Discussionmentioning
confidence: 99%